2017
DOI: 10.1177/1538192717697755
|View full text |Cite
|
Sign up to set email alerts
|

Mentors, Resiliency, and Ganas

Abstract: Emerging research has explored the psychological and emotional challenges undocumented students encounter while accessing higher education, yet few studies have specifically investigated the factors that facilitate success once admitted. Semistructured interviews with former or current undocumented students suggest that factors such as mentors, individual resiliency, and the ganas to succeed affect students' navigation strategies in higher education. Interviewees suggest solutions to institutional barriers tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 26 publications
(28 reference statements)
0
31
0
Order By: Relevance
“…Future studies with qualitative approaches are needed to better capture the nature of these community assets and the mechanisms by which these meso-and exo-sytem influences support the development of hope, and other resilient characteristics, among immigrant students and undocumented students (Su arez-Orozco et al, 2011). For example, Gamez, Lopez, and Overton (2017) discuss mentors can promote resiliency and success of undocumented students in higher education.…”
Section: Resultsmentioning
confidence: 99%
“…Future studies with qualitative approaches are needed to better capture the nature of these community assets and the mechanisms by which these meso-and exo-sytem influences support the development of hope, and other resilient characteristics, among immigrant students and undocumented students (Su arez-Orozco et al, 2011). For example, Gamez, Lopez, and Overton (2017) discuss mentors can promote resiliency and success of undocumented students in higher education.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the outside resources of strong faculty relationships and school support systems contributed to their success as well. Recent research studies (Borjian, 2018;Gámez et al, 2017) lend support to earlier research (Fergus & Zimmerman, 2005;Zimmerman, 2013) asserting that family, school, and community support systems, along with the personal motivation and inward desire to succeed, were some factors that contributed the resiliency of UIC.…”
Section: Discussionmentioning
confidence: 61%
“…Research on resiliency and immigrant students have looked at what makes these students academically successful in primary grades through college, internationally as well as in the United States. For example, a recent study by Gámez, Lopez, and Overton (2017) explored the factors influencing the success of undocumented students in higher education, They concluded in their findings that factors such as having mentors, resiliency, and ganas-"internal motivators" (p. 156) contributed to the successful navigation of college experiences for these students. Similiarly, the results of a qualitative study focusing on the academic success of eight undocumented students at a U.S. college conducted by Borjian (2018) revealed that pro-immigrant policies, institutional processes, and support, particularly from family, were important factors in developing academic resiliency of the participants.…”
Section: Theoretical Overviewmentioning
confidence: 99%
“…This macrosytemic context has shaped societal attitudes toward immigrants, resources, and the opportunity structure for students (14) and has implications for a host of outcomes including educational trajectories and psychological wellbeing (23). While recognizing the extraordinary resilience of undocumented youth, the stressors they are facing at this macrosystemic level place them at heightened psychological risk (12,14,23,24).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…An exception to this generalization is regards to a body of scholarship with undocumented college students who currently constitute an estimated quarter of a million students in the United States (10). While this growing and rich body of work has qualitatively explored the experience of both stress and resilience among these students (11,12), there have been few studies to date, that have attempted to gauge potential rates of anxiety amongst them [(13), for an exception].…”
Section: Introductionmentioning
confidence: 99%